Penyiaran Islam di Daerah Perbatasan "Badau" Indonesia-Malaysia - Zakaria Efendi (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2017)
Badau is a region in Indonesia located in the Regency of Kapuas Hulu, West Kalimantan bordering directly with Malaysia. In the Badau District, there is one luxurious border post (PLBN) used by Indonesian and Malaysian citizens to conduct interstate border crossings. Islam is a minority religion in Badau as the native residents living in Badau are the Dayak Iban tribe who are mostly Catholics and some are Protestants, with Islam being a religion embraced by locals of Melayu descent and some converts from the Dayak Iban as well as new comer ethnic groups such as Javanese, Bugis, Batakese, and others. Dakwah (proselytizing of Islam) does not easily reach Badau, due to the fact that there was no interstate dakwah conducted by ulemas from Malaysia. As a region remotely separated from the provincial capital of West Kalimantan, that is Pontianak, the dakwah efforts in Badau were confronted by numerous obstacles such as a time consuming distance of travel by land transport and very difficult terrains. Although Islam is a minority religion there, tolerance is still maintained and a mutual sense of respect among ethnicities, races, and religions has made Badau into a safe border area.[Badau merupakan wilayah di Indonesia yang terletak di Kabupaten Kapuas Hulu, Kalimantan Barat yang berbatasan langsung dengan Malaysia. Di kecamatan Badau terdapat satu PLBN megah yang digunakan oleh warga Indonesia dan Malaysia untuk melakukan penyeberangan lintas Negara. Islam menjadi Agama minoritas di Badau, karena memang penduduk asli yang tinggal di Badau adalah suku Dayak Iban yang beragamakan Katholik, dan sebagian lagi beragamakan Kristen, dan Islam menjadi Agama yang di peluk oleh masyarakat Asli yang bersuku Melayu dan sebagian mualaf dari bangsa Iban suku Dayak, dan suku-suku pendatang seperti Jawa, bugis, Batak dan sebagainya.. Meskipun terletak di perbatasan tidak membuat Dakwah dengan mudah sampai di Badau, hal ini disebabkan tidak adanya dakwah antar Negara yang dilakukan oleh Ulama-ulama dari Malaysia. Wilayah yang jauh dari jangkauan Ibu Kota Kalimantan Barat, Pontianak, menjadikan Penyiaran Islam di Badau mendapat kendala, karena jarak tempuh darat yang memakan waktu cukup lama dan medan yang masih sulit. Meskipun Islam menjadi Agama minoritas, namun toleransi tetap terjaga, sikap saling menghargai antar etnik,suku, dan agama menjadikan daerah Badau adalah daerah perbatasan yang aman.]